2009
DOI: 10.1590/s0102-67202009000400006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patients with schistosomal portal hypertension treated in a tertiary hospital

Abstract: BACKGROUND: Schistosomiasis is an important public health issue in more than 70 countries around the world. About 600 million people are at risk to acquire the parasite and there are 200 million infected worldwide. AIM: To evaluate the characteristics of schistosomal portal hypertension individuals who underwent previous esophageal varices bleeding treated in a tertiary hospital. METHODS: The records of 155 patients were evaluated and clinical, laboratorial, endoscopic, epidemiological features and hemorrhagic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Studies using portal vein ligation in rats demonstrated a long-term effect of portal flow deprivation on mRNA expression of proliferative and angiogenic factors in the liver, indicating a potential association with liver carcinogenesis 13,14 . Another study showed an association of PVT with the development of liver lesions, including benign liver tumors, such as focal nodular hyperplasia and hepatocellular adenoma, and malignant liver tumors, such as HCC and hepatoblastoma 15,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies using portal vein ligation in rats demonstrated a long-term effect of portal flow deprivation on mRNA expression of proliferative and angiogenic factors in the liver, indicating a potential association with liver carcinogenesis 13,14 . Another study showed an association of PVT with the development of liver lesions, including benign liver tumors, such as focal nodular hyperplasia and hepatocellular adenoma, and malignant liver tumors, such as HCC and hepatoblastoma 15,17 .…”
Section: Discussionmentioning
confidence: 99%